The Efficacy and Undesired Effects of High Dosage Zinc Treatment - Guvenc Kockaya, Baran Ufuktepe, Pinar Daylan Kockaya, Selcuk Sen, Ozlem Altunel, Yagiz Uresin (Journal of Applied Pharmaceutical Science)
Zinc is an essential micronutrient for human health. It is very important for body functions, and they have an interaction potential in several systems, including nervous system. Although there is no global regulation about the daily amounts, it is shown to reduce the incidence of diarrhea and pneumonia. Zinc deficiency is a global problem, especially in developing countries. Zinc has been shown to be effective in treatment of zinc deficiency, Acrodermatitis Enteropathica, protein energy malnutrition (PEM), Wilson disease, pica, diarrhea, unrecovering ulcers etc. Although under 50 mg daily is enough for diarrhea, anemia, infections, immundeficieny etc., higher dosages may be required in Wilson`s disease, pica and acrodermatitis enteropathica up to 220 mg daily. Also it was reported that high dosage of zinc treatment can lead neurotoxity, Alzheimer`s disease or impaired lipid metabolism. So caution should be exercised when prescribing the zinc to the patients who have risk for neurotoxity, Alzheimer`s disease or impaired lipid metabolism.
Keywords: Zinc Treatment,micronutrient,Zinc deficiency.